PEDAGOGIKALIQ KOMMUNIKATIV MÁDENIYATI BOLAJAQ OQITIWSHINIŃ KÁSIPLIK TAYARLIǴIN JETILISTIRIWDIŃ SHÁRTI SIPATINDA - Saytbekova, S.; Jetesova, A.; Djumaniyazova, D. (SCIENCE and SOCIETY, 2022)
This article states about the formation and improvement of a pedagogical communicative culture of future teachers with students in the process of communication and learning.